2018
DOI: 10.1039/c7md00565b
|View full text |Cite
|
Sign up to set email alerts
|

5,6-Benzoflavones as cholesterol esterase inhibitors: synthesis, biological evaluation and docking studies

Abstract: In a continued effort to develop potent cholesterol esterase (CEase) inhibitors, a series of 5,6-benzoflavone derivatives was rationally designed and synthesized by changing the position of the benzene ring attached to the flavone skeleton in previously reported 7,8-benzoflavones. All the synthesized compounds were checked for their inhibitory potential against cholesterol esterase (CEase) using a spectrophotometric assay. Among the series of forty compounds, seven derivatives (- to -) exhibited above 90 perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Flavones have many functions. They are a strong antioxidants whose capacities are more than 10 times that of vitamin E. They effectively remove oxygen free radicals in the body ( Popovic et al, 2019 ), prevent cell degeneration and aging, and prevent cancer ( Mazewski et al, 2018 ; Chen et al, 2020 ); they also improve blood circulation and lower cholesterol ( Singh et al, 2018 ), inhibit the exudation of inflammatory enzymes, promote wound healing, and relieve pain ( Shoaib et al, 2019 ). Isoflavone is a flavonoid that mainly exists in leguminous plants.…”
Section: Introductionmentioning
confidence: 99%
“…Flavones have many functions. They are a strong antioxidants whose capacities are more than 10 times that of vitamin E. They effectively remove oxygen free radicals in the body ( Popovic et al, 2019 ), prevent cell degeneration and aging, and prevent cancer ( Mazewski et al, 2018 ; Chen et al, 2020 ); they also improve blood circulation and lower cholesterol ( Singh et al, 2018 ), inhibit the exudation of inflammatory enzymes, promote wound healing, and relieve pain ( Shoaib et al, 2019 ). Isoflavone is a flavonoid that mainly exists in leguminous plants.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it is generally characterized by severe adverse effects including gastrointestinal intolerances, which can harm up to 40% of patients [ 47 ]. Multiple potent ChEase inhibitors, such as phosphonates and carbamates, have lately emerged, but lack selectivity [ 48 ]. As a result, patients would benefit tremendously from a medicine that suppresses PL and ChEase while reducing or eliminating negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating its efficacy in averting known treats of diabetes mellitus-related cardiac complications [ 21 , 61 ]. Flavonoids [ 48 ] and anthraquinones [ 62 ] detected in G. lotoides have been attributed to blood TG, TC, LDL-c, and VLDL-c reduction. Hence, its antidyslipidaemic effect may be due to those bioactive constituents .…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by the formation of oxyethylene ylide In contrast to the intramolecular cyclization of ylide intermediates, an alternative pathway involves a dipolar cycloaddition reaction. In 2022, Jin et al reported a method involving the dual functionalization of a tertiary amine's C(sp 3 )-H bonds. 28 This process entailed hydride transfer-induced dehydrogenation followed by cycloaddition, utilizing readily prepared diazo esters as a novel precursor for hydroxide receptors, all achieved under mild redox-neutral conditions.…”
Section: A-diazo Esters As Carbene Precursorsmentioning
confidence: 99%
“…Heterocyclic compounds hold substantial importance in natural isolates, potential drug candidates, and the development of functional materials. [1][2][3][4][5] Therefore, the development of robust techniques for their facile synthesis, particularly for the construction of chiral heterocyclic compounds is an area of fundamental research importance in synthetic chemistry. Over the past few decades, transition metal-catalyzed or mediated cyclization reactions have surfaced as a highly efficient method for constructing heterocyclic skeletons.…”
Section: Introductionmentioning
confidence: 99%